SISTEMATIZAÇÃO DA PRODUÇÃO DOS SABERES: A DANÇA NO ESPAÇO ESCOLAR EM DIÁLOGO COM STRAZZACAPPA - FIGUEIRÓ, Mel Luiz Batista; MENEGHEL, Renata Lopes; SILVA, Maria Eduarda Flores da; ZUBIETA, Eduarda Alves e Silva; SOUZA, Yasmin Fróes de; BAPTISTELLA, Rosana (ANAIS DO ENIC, 2024)
-